Visual Functions among amplyopic patients - Shrestha, Sabina; Sharma, Dikchhya; Manoranjan, Aparajita; Joshi, Subee; Shrestha, Yuliya (Nepal Medical College Journal, 2023)
Apart from decreased visual acuity, amblyopia may be associated with alteration in color vision, contrast sensitivity and stereopsis. The study was conducted to assess visual functions among amblyopic patients. Cross sectional observational study was done with appropriate examination. Best corrected visual acuity, color vision, contrast sensitivity and stereopsis were done among 31 amblyopic patients of age 5-18 years, visiting Department of Ophthalmology in Kathmandu Medical College from October 2021 to March 2022. Among thirty-one patients, male is to female ratio was 1.81:1. Mean age of participants was 9.45±3.49 years. Among patients with stimulus deprivation amblyopia, visual acuity was <6/60, color vision and contrast sensitivity were decreased in 100% and moderate stereopsis (80-200 seconds of arc) was present. Among patients with strabismic amblyopia, visual acuity was decreased (6/12-6/18), color vision and contrast sensitivity were normal in 100% and good stereopsis (<60 seconds of arc) was seen. Among those with refractive amblyopia, visual acuity was 6/6-6/9 in 34.5%, 6/12-6/18 in 44.8% and 6/24-6/60 in 20.7%. Color vision was decreased in 27.3% in ametropic, 9.1% in meridional and normal in anisometropic type. Contrast sensitivity was decreased in 27.3% each in ametropic and anisometropic, and in 63.6% in meridional amblyopia. Good and poor (>200 seconds of arc) stereopsis was found in 24.1% each and moderate in 51.7% of refractive amblyopia. Contrast sensitivity was seen to be decreased with decrease in vision (40.0%, 42.8%, 50.0% and 100.0% in visual acuity 6/6-6/9, 6/12-6/18, 6/24-6/60 and<6/60 respectively). To conclude, visual functions are affected in different types of amblyopia.